THEORETICAL PERSPECTIVES ON THE PARTONYMIC (HOLO-MERONYMIC) PHENOMENON IN ENGLISH AND UZBEK LANGUAGES - Jovbo‘riyeva Saodat O‘ktamovna; Xolliyeva Mashxura Erkinjonovna (Modern American Journals, 2025)
This article presents theoretical perspectives on when the concept of the partonymic (holo-meronymic) phenomenon first emerged in English and Uzbek linguistics, the stages of its development, and its introduction into the field of linguistics.
Keywords: Meronym, partonym, holonym, part-whole relationship, partonymic lexical meaning, system lexicology